Central bank swaps then and now: swaps and dollar liquidity in the 1960s - Catherine Schenk; McCauley, RN (Bank for International Settlements, 2020)
This paper explores the record of central bank swaps to draw out four themes. First, this recent device of central bank cooperation had a sustained pre-history from 1962-1998, surviving the transition from fixed to floating exchange rates. Second, Federal Reserve swap facilities have generally formed a part of a wider network of central bank swap lines. Third, we take issue with the view of swaps as previously used only to manage exchange rates and only more recently to manage offshore funding liquidity and yields. In particular, we spotlight how in the 1960s the Federal Reserve, working in conjunction with the BIS and European central banks, repeatedly used swaps to manage eurodollar funding liquidity and Libor yields. BIS, Bank of England and Swiss National Bank archives show an intention to offset seasonal disturbances to funding liquidity in order to prevent eurodollar yield spikes. Fourth, this earlier cooperation underscores the Federal Reserve’s use of swaps to prevent eurodollar shortages from interfering with the transmission of its domestic monetary policy. The US interest in the eurodollar market, and thus its self interest in central bank cooperation, is unlikely to end even when Libor is replaced as the benchmark for US floating-rate loans and mortgages.